PENGARUH MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR PADA KELAS V SDN 02 LEMBAH MELINTANG PASAMAN BARAT - Makpiroh Izanni; Dini Maielfi; Khairul Ikhwan; Ilham Adi Putra; Andika Bayu Putra (STKIP Subang, 2025)
This research was motivated by the lack of innovation in the selection of learning models in science subjects, which are still dominated by lecture methods, resulting in low learning outcomes of fifth-grade students at SDN 02 Lembah Melintang, Pasaman Barat. The purpose of this study was to determine the effect of the cooperative learning model Teams Games Tournament (TGT) assisted by Wordwall media on science learning outcomes in the human respiratory system topic. This study employed a quasi-experimental method with a posttest-only control group design. The population consisted of all fifth-grade students, with class VA as the control group using conventional learning and class VB as the experimental group using the TGT model assisted by Wordwall. The research instrument was a multiple-choice test consisting of 20 items, while data were analyzed using an Independent Sample t-Test with SPSS 27. The results indicated that the data were normally distributed and homogeneous. The t-test analysis obtained a significance value of 0.000 (< 0.05), which means that there was a significant difference between the science learning outcomes of the experimental and control groups. Therefore, it can be concluded that the implementation of the TGT model assisted by Wordwall has a positive effect on improving the science learning outcomes of fifth-grade students.